The Meaning of learning for students with special needs (phenomenological study at LSBA Jakarta - Indonesia) - Rachmawati, Dewi; Chrisdina,; Fitriyani, Lamria Raya; Oktaviani, Rani Chandra (Penerbit Universiti Kebangsaan Malaysia, 2024)
Education is the right of every person to improve the quality of themself through a comfortable atmosphere and environment. For students with special needs, this greatly influences progress both in terms of skills and how learning is interpreted. London School Beyond Academy (LSBA) is a skills education institution that has succeeded in forming special needs students to be able to enjoy the teaching and learning process through a conducive environment and understand them well. The purpose of this research is to find out the meaning of learning for special needs students who attend LSBA. Through Alfred Schutz's thinking, this study found that the intersubjective or everyday world is an element that plays a role in the thinking of special needs students in understanding meaning. This study uses a qualitative method with a phenomenological study by selecting four special needs students, three lecturers and one parent. There are five themes that come up in this research for the meaning of learning for special needs students. The themes are increasing knowledge and becoming smarter, making more friends, having fun, achievement and learning because of parents. The supporting factors for learning for students with special needs are parents as the main ones, then siblings, the school environment, extended family, people closest to them other than family and friends. The self-concept of students with special needs examined in this research shows a positive self-concept. This research provides benefits for schools, parents and all other related parties in understanding students with special needs in learning.